CORRUPTION AND ITS EFFECTS ON THE ECONOMY AND PUBLIC SECTORS - Vita Kartika Sari; Mugi Rahardjo (MESP–FEB UNS, 2019)
Corruption is an ancient problem and its levels vary greatly across countries. Many factors contribute to corruption, including individual behavior, government organization, law enforcement, and weakness of controlling. The objectives of this study are to identify the social cost of corruption and investigate the impact of corruption on the public and economic sectors. A literature survey was conducted in this study. We figured out that corruption occurs not only at the central government level but also at the regional government level, along with regional autonomy. Corruption has affected economic growth, the level of GDP per capita, investment activity, international trade and price stability negatively. Corruption has also abused public budget to private or group interest. Keywords: Corruption, The Social Cost Of Corruption, Misallocation Of Resources.